Timeline and Incidence of Infectious Complications in Older Transplant Recipients During the First Year Post-Transplantation - Caglayan Merve Ayaz; Serdar Ceylan; Vural Taner Yılmaz; Haydar Adanır; Özge Turhan (Pathogens, 2024)
The number of older adults undergoing organ transplantation, and waiting lists are increasing. The epidemiological data on infections in older transplant patients are scarce. The objective of the study was to investigate the incidence and distribution of infectious complications in older patients according to post-transplant periods. This retrospective study was conducted in a university hospital between 1 January 2018 and 31 March 2023. All infectious episodes were analyzed over three post-transplant periods. Forty-four patients were enrolled. The median age was 67 years (min: 65 and max: 87 years). Patients experienced a total of 98 infectious episodes. The median number of infectious events per patient was 1.0 (min: 0 and max: 8). The overall incidence rate of infectious events was 2.18 infectious episodes per 1000 transplant days. Of the patients at risk, 18.2% had 12 (12.4% of all infections) infections in the first month (9.09 episodes per 1000 transplant days), 56.8% had 52 (53.1%) infections between 1 and 6 months (7.88 episodes per 1000 transplant days), and 40.9% had 34 (35%) infections >6–12 months post-transplant (0.92 episodes per 1000 transplant days) The most prevalent type of infection was bacterial (79.6%, n = 78) followed by viral (18.4%, n = 18) and fungal (2.0%, n = 2) infections. The overall mortality rate of the 44 patients was 13.6%. The bacterial infections were more prevalent, and the incidence of infection was high during all post-transplant periods. These results may guide infection management in older transplant patients.